La tortura y trato degradante a los animales - Escobar Chango, Guido Fabián (2012)
Animals have rights protection enshrined in the Constitution of the Republic of Ecuador when it comes to the rights of nature, of the legal protection of wildlife is established in International Treaty called The Universal Declaration of Animals. The thesis main objective is to make a proposal to reform the Criminal Code that punish more severely the acts torture and degrading treatment of domestic animals, for in Ecuadorian law sanctions are very flexible on this issue and otherwise empty laws that allow them to proliferate acts of animal abuse. The study begins with the theoretical framework, it included the historical, doctrinal and legal framework in which latter has been made legal and doctrinal analysis of criminal law imposed for acts of torture and degrading treatment of animals in order to establish whether Ecuador regulates and punishes violations committed against animals. To achieve the objective of this thesis has been carried out field research in the Canton La Mana of the Province of Cotopaxi, where we have used the scientific method, and as research tools, surveys and interviews that we have identified the most common forms of animal abuse, including legal thoughts of the Fourth Judge of Criminal Guarantees of La Mana city. Based on the information processed and systematized designing the proposed amendments to Article 414 of the Criminal Code of Ecuador.